MODIFICATIONS OF MAXIMUM POWER POINT TRACKING P&O METHOD FOR PHOTOVOLTAIC PANEL - Kozierski, Piotr; Owczarkowski, Adam; Lis, Marcin; Horla, Dariusz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2018)
Perturbation and Observe method for maximum power point tracking is presented in this paper. Three method modifications have been proposed, which allow satisfying tracking efficiency, even for very fast and noisy irradiance changes.